2010
DOI: 10.1017/s0272263110000033
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Range and Frequency of Occurrence of Forms in Potentially Variable Structures in Second-Language Spanish

Abstract: This article adds to the growing body of research focused on second-language (L2) variation and constitutes the first large-scale study of the production of potentially variable grammatical structures in Spanish by English-speaking learners. The overarching goal of the project is to assess the range of forms used and the degree to which native and L2 speakers of Spanish differ in several independently defined syntactic or discourse-based contexts. The contexts examined in the current study have been the object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…Subjunctive vitality was also found in studies conducted with NSs currently residing in the U.S. (Geeslin & Gudmestad 2010;Gudmestad 2010Gudmestad , 2012. However, in terms of frequency, Geeslin and Gudmestad (2010) indicated that their native speaker (NS) participants favored non-subjunctive forms significantly more than subjunctive forms.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…Subjunctive vitality was also found in studies conducted with NSs currently residing in the U.S. (Geeslin & Gudmestad 2010;Gudmestad 2010Gudmestad , 2012. However, in terms of frequency, Geeslin and Gudmestad (2010) indicated that their native speaker (NS) participants favored non-subjunctive forms significantly more than subjunctive forms.…”
Section: Introductionmentioning
confidence: 64%
“…However, in terms of frequency, Geeslin and Gudmestad (2010) indicated that their native speaker (NS) participants favored non-subjunctive forms significantly more than subjunctive forms. A total of 8,716 tokens were identified for the data collected during an oral elicitation interview, of which 586 (6.7%) were subjunctive forms.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Bayley and Tarone (in press) review variationist SLA studies and conclude that these show that much of the variation that we see in learner language is systematic. Variation in interlanguage production, documented in dozens of variationist studies, certainly has profound implications for data elicitation and analysis in research (Preston, 1989(Preston, , 2002Tarone, 2007;Geeslin & Gudmestad, 2010). Variationist researchers argue that because production of given interlanguage forms varies systematically in relation to accompanying linguistic variables, task, topic, focus on form, interlocutor, and so on, then researchers need document the contextual factors in play in each elicitation, and use sophisticated statistical tools to model interlanguage.…”
Section: The Revised Interlanguage Hypothesismentioning
confidence: 99%
“…While maintenance of subjunctive use has been observed in several regional varieties (Fernández-Ulloa & Portillo Mayorga, 2000;Gallego & Alonso Marks, 2014;Gudmestad, 2006Gudmestad, , 2010Gudmestad, , 2012Geeslin & Gudmestad, 2010;Kowal, 2007;Lastra & Butragueño, 2012), the predominance of nonsubjunctive forms in subjunctive-triggering contexts appears to be more prevalent in varieties of Spanish spoken in the U.S. (Lynch, 2000;Martínez Mira, 2009;Mikulski, 2010;Montrul, 2009;Silva-Corvalán, 1991, 1994, 2001.…”
Section: Introductionmentioning
confidence: 99%